Multifaceted Beauveria bassiana and Other Insect-Related Fungi - Nicolás Pedrini; Éverton K. K. Fernandes; Ivan M. Dubovskiy (Journal of Fungi, 2024)
Since Agostino Bassi first isolated the fungal pathogenic agent of the white muscardine in insects (later named Beauveria bassiana in his honor), and Ilya Mechnikov cultivated Metarhizium anisopliae as a first approach to use fungi as pest control agents, many other entomopathogenic fungi have been studied over the last two centuries [...]